THE INFLUENCE OF WATCHING SOCCER COMPETITION IN TELEVITION TOWARD CHILD'S SOCIAL BEHAVIOR IN PLAYING SOCCER - Cendra, Romi (2014)
Television mass media is very influential toward child behavior seen from object she/he likes, one of them is watching soccer competition. This study aim to find out the influence of soccer competition in television toward child's social behavior in playing soccer. The method of study which is used is ex post facto with causal-comparative research design which compare child who often watch and child who seldom watch soccer competition in television toward his/her social behavior in playing soccer. Population in this study is SMAN 4 Garut, Garut Regency, West Java Province with sample as much as 21 severe watcher and 21 mild watcher who are selected in purposive sampling after questionnaire is distributed to all populations as much as 150 students. From result of data analysis it can be concluded that severe watcher/often watch soccer competition in television is influential toward child's social behavior in playing soccer with its significance value is 0.019. This is show significance < 0.05 and seen from mean score value of child's social behavior group of severe /often watcher is bigger than child's social behavior group of mild/seldom watcher with score is 146.52 > 135.05. Therefore, the significant difference is seen between child's social behavior (severe/often watcher) with mild/seldom watcher in playing soccer. Media massa televisi sangat berpengaruh terhadap perilaku anak dilihat dari objek yang dia sukai, salah satunya menonton pertandingan sepakbola. Penelitian ini bertujuan untuk mengetahui pengaruh pertandingan sepakbola di televisi terhadap perilaku sosial anak dalam bermain sepakbola. Metode penelitian yang digunakan adalah ex post facto dengan design penelitian causal-comparative yang membandingkan anak yang sering menonton dan anak yang jarang menonton pertandingan sepakbola di televisi terhadap perilaku sosialnya dalam bermain sepakbola. Populasi dalam penelitian ini adalah SMAN 4 Garut Kabupaten Garut Provinsi Jawa Barat dengan sampel 21 orang penonton berat dan 21 orang penonton ringan yang dipilih secara purposive sampling setelah angket disebarkan kepada seluruh populasi yang berjumlah 150 orang siswa. Dari hasil analisis data dapat disimpulkan bahwa penonton berat/sering pertandingan sepak bola di televisi berpengaruh terhadap perilaku sosial anak dalam bermain sepakbola dengan nilai signifikansinya 0.019. Hal ini menunjukkan signifikansi < 0.05 dan dilihat dari nilai skor rata-rata (mean) kelompok perilaku sosial anak penonton berat/sering lebih besar dari kelompok perilaku sosial anak penonton ringan/jarang dengan skor 146.52 > 135.05. Dengan demikian terlihat perbedaan yang signifikan antara perilaku sosial anak penonton berat/sering dengan anak penonton ringan/jarang dalam bermain sepakbola.